Efficient single particle detection with a superconducting nanowire - Hatim Azzouz; Sander N. Dorenbos; Daniel De Vries; Esteban Bermúdez Ureña; Valery Zwiller (AIP Advances, 2012)
Detection of α- and β-particles is of paramount importance in a wide range of applications. Current particle detectors are all macroscopic and have limited time resolution. We demonstrate a nanoscale particle detector with a small detection volume, high detection efficiency, short dead times and low dark count levels. We measure α- and β-particle detection efficiencies close to unity using different sources and also demonstrate blindness towards γ-rays. Our nanoscale detector offers particle detection measurements with unprecendented spatial resolution.